Sinergitas Pemerintah Dan Masyarakat Dalam Mewujudkan Desa Sadar Kerukunan Umat Beragama Di Desa Lumbirejo Dan Desa Poncokresno Negeri Katon Pesawaran Lampung - Ruslan, Idrus; Rosana, Ellya (AL-ADYAN, 2024)
Diversity is a characteristic and treasure of the Indonesian nation. Religious differences are like a double-edged knife, one side is wealth and the other can trigger conflict in people's lives. As a large and diverse nation, we must be able to manage existing diversity in order to sustain harmonious social life. This research displays the synergy between the government and society in creating a village aware of religious harmony in Lumbirejo Village and Poncokresno Village, Negeri Katon District, Pesawaran Regency. This research uses a qualitative approach. In collecting data, researchers conducted interviews and observations in the field and in book literature, scientific journal articles and other written sources. The results of this research show that in creating a village aware of religious harmony, the Lumbirejo Village and Poncokresno Village Governments are synergizing with the Pesawaran FKUB, Pesawaran Ministry of Religion, Pesawaran Regency Government, TNI and Polri. The supporting factors are; First, an understanding of society that is aware of differences, tolerant and united is the main capital for realizing a harmonious society; Second, synergy between government and society. The next obstacle factors in realizing a harmonious conscious village are: First, political interests; Second, social media content that contains SARA has a bad influence on young people; Third, the lack of government operational assistance to FKUB Pesawaran as a means of realizing a village that is aware of religious harmony has therefore not been maximized.